PERLINDUNGAN HUKUM PIHAK KETIGA (PENYEWA) TERHADAP INVESTOR AKIBAT TIDAK MELEPASKAN HAK GUNA BANGUNAN PASCA PEMUTUSAN KONTRAK BAGI TEMPAT USAHA - Rexon Manihuruk; Tri Lisiani Prihatinah; Sulistyandar Sulistyandar (Jurnal Idea Hukum, 2020)
Uncertainty of the status of the building rights after the termination of the contract for the place of business has an impact on third parties (tenants) who do not get certainty to who pays the lease obligations. Each party, both from the Tegal City Regional Government and the Investor claim as the right party. Even since the settlement of the peace agreement for the implementation of the Reinjection Decision Number 413/PK/Pdt/2008 (from the Investor's lawsuit against the Tegal City Government) after the termination of the contract for the place. The tenant gets uncertainty again when the Investor's lawsuit against the tenant after receiving the morning market compensation from the Tegal City Government, increasingly becomes unclear the status of the HGB for the stall occupied.This study uses a normative juridical approach to analyze court decisions andtermination of agreements and legal protection. The research specification is descriptiveanalytic and the analysis is based on secondary data. Termination of the contract for the place of business does not necessarily mean that the status of the HGB has also been transferred. This must bedone with the release of rights as regulated in Article 35 of Government Regulation Number 40 of 1996, Land Use Rights, Building Use Rights, and Land Use Rights, namely paragraph 1 (c) , in the case of the author who raised the status of the HGB above the HPL of Block B and C of the Tegal City Morning Market after the termination of the contract for the place of business is still on behalf of the Investor as the rights holder. Legal protection for third parties/tenants is the first repressive form of protection which is reflected in the objection ruling Decision Objection. Number 7/Pdt.G.S/2018/PN. The Tegal District Court's claim from an investor that was declared unacceptable refers to the implementation of a peace agreement between the Tegal City Government and the Investor.